Application of the Potentiometric Stripping Analysis with Constant Current for the Determination of Lithium Ions Using a Spinel-Type Manganese (IV) Oxide-Modified Carbon Paste Electrode - Teixeira, Marcos F. S. [UNESP]; Bergamini, Marcio F.; Bocchi, Nerilso (Bentham Science Publ Ltd, 2010)
A potentiometric stripping method for the measurement of lithium ions at a carbon paste electrode modified with spinel-type manganese oxide is described. The procedure is based on the effective pre-concentration of lithium ions on an electrode surface containing spinel-type MnO(2), with the reduction of Mn(IV) to Mn(III), and the consequent intercalation (insertion) of the lithium ions into the spinel structure. The best current constant stripping analysis (CCSA) response was reached for an electrode composition of 25% (m/m) spinel-type MnO(2) in the paste, 0.1 mol L(-1) TRIS buffer solution at pH 8.0, an accumulation potential of 0.3 V vs. the saturated calomel reference electrode (SCE), a pre-concentration time of 90 s and the application of a small positive constant current (10 A) during the stripping step. The obtained limit of detection was 2.0 x 10(-7) mol L(-1), and the relative standard deviation from five measurements of 2.5 x 10(-6) mol L(-1) lithium ions was 3.8%.
Keywords: Lithium ions; Spinel-type manganese oxide; Potentiometric stripping analysis